ANALYSIS OF FACTORS AFFECTING FARMING PRODUCTIVITY OF RAWA LEBAK RICELAND BASED ON LAND TYPOLOGY IN GANDUS DISTRICT, PALEMBANG CITY - Novayanti Yusni; Laila Husin; Dwi Wulan Sari (BIOVALENTIA: Biological Research Journal, 2022)
Most of the paddy fields in the city of Palembang are rawa lebak land that scattered on the banks of the Musi River. One of the centers of rawa lebak rice in Palembang City is in Gandus District, which has an area of 1,017,255 hectares of rawa lebak rice fields.  The productivity of rawa lebak rice in Gandus District (4.4 tons/ha) is still lower than the average productivity of South Sumatra Province (4.975 tons/ha) and national (5.13 tons/ha). The purpose of this study was (1) to analyze the factors that influence rice production in rawa lebak rice farming in three typologies, namely  shallow, middle, and deep rawa lebak land, and (2 ) to analyze the efficiency of the use of rice production factors in rawa lebak rice farming in three typologies of rawa lebak land. The research was conducted in Gandus District, Palembang City. Sampling used purposive sampling method and taken as many as 93 farmers, consisting of 31 farmers in each rawa lebak typology.  The analysis used is a Cobb-Douglass model regression and t-test to determine the effect of production factors, and efficiency analysis to determine the efficiency of the use of production factors. The results showed that (1) The production factor of urea and NPK fertilizers had a significant affect on farming productivity in all   typologies of rawa lebak land.  Land area, seed, and pesticide factors had no significant effect on farming productivity  in all typologies of rawa lebak land. Meanwhile the labor factor had a significant effect in middle and deep rawa lebak land, but had no significant effect in shallow rawa lebak land.(2) The production factors of land area and seeds are inefficient in all land typologies. The production factor of urea  and NPK fertilizer has not been used efficiently in all land typologies. The use of pesticide factor is inefficient in the middle and deep rawa lebak land, while the use of labor is inefficient in the shallow and deep rawa lebak land.